1/4 2/8 3/12 4/16 5/20 6/24
y = -1 + 3/8x
2x - 5y = 6
Substitute the first equation into the second equation, since y is already by itself.
2x - 5(-1 + 3/8x) = 6
2x + 5 - 15/8x = 6
2x - 15/8x = 1
16/8x - 15/8x = 1
1/8x = 1 Multiply 8 on both sides to get x by itself
x = 8
Plug x into either of the equations.
y = -1 + 3/8(8)
y = -1 + 3
y = 2
2(8) - 5y = 6
16 - 5y = 6
-5y = -10
y = 2
(8,2)
Answer:
1) one
2) zero
Step-by-step explanation:
e/sinE = g/sinG
10/sin64 = 9/sinG
sinG = 0.8089146417
G = 53.99
j/sinJ = k/sinK
3/sin129 = 8/sinK
sinK = 2.072389241
Is this a true or false question?
45/75 = 30/x
30*75 = 2250/45 = 50
EF = 50 in.